2004
DOI: 10.1161/01.hyp.0000141439.34834.84
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of JNC VI Guideline Adherence, Intensity of Drug Therapy, and Blood Pressure Control by Race and Ethnicity

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
72
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 23 publications
9
72
2
Order By: Relevance
“…Several studies reported that men achieved better control, others showed that female sex is a predictor of treatment success and some found no differences between the sexes. [34][35][36][37][38] In our study, no significant differences of BP control between men and women under treatment were found over time. However, 70% of our patients were women and this finding is consistent with a systematic review that showed that in developing countries, overall, women were more aware of their hypertension status and more likely to get pharmacological treatment.…”
Section: Discussioncontrasting
confidence: 63%
“…Several studies reported that men achieved better control, others showed that female sex is a predictor of treatment success and some found no differences between the sexes. [34][35][36][37][38] In our study, no significant differences of BP control between men and women under treatment were found over time. However, 70% of our patients were women and this finding is consistent with a systematic review that showed that in developing countries, overall, women were more aware of their hypertension status and more likely to get pharmacological treatment.…”
Section: Discussioncontrasting
confidence: 63%
“…9 Given the low rate of adherence, it is not surprising that only 30 to 60% of patients are at goal blood pressure. 4,6,[10][11][12][13] These data come from studies that evaluated hypertensive management in the outpatient setting. No study has evaluated adherence to hypertension guidelines or blood pressure control rates among nursing home residents.…”
Section: Introductionmentioning
confidence: 99%
“…In a study published in 2004, we examined patients receiving care in these settings and found that blood pressure remained poorly controlled among only 36% of hypertension-related visits, although patients were receiving a JNC-recommended medication for 81% of visits. 14 We also found that minorities were more likely to have poorly controlled hypertension despite being more likely to receive a guideline-recommended drug. Secondary analyses of these data determined that Hispanics, the racial/ethnic group with poorest control, were less likely to have had their therapy appropriately intensified at any time over a 1-year period and that intensification of therapy was highly correlated with obtaining subsequent blood pressure control.…”
Section: Discussionmentioning
confidence: 51%
“…Secondary analyses of these data determined that Hispanics, the racial/ethnic group with poorest control, were less likely to have had their therapy appropriately intensified at any time over a 1-year period and that intensification of therapy was highly correlated with obtaining subsequent blood pressure control. 14,29 Future interventions aimed at increasing rates of appropriate antihypertensive intensification should be studied to determine whether such CDS can improve hypertension outcomes and future studies aimed at reducing disparities may require more intensive, nonclinic-based interventions to overcome factors that pose particular challenges for traditionally underserved patients, such as lack of access to medications, medical mistrust, and environmental stress. 15,30 Focusing solely on blood pressure control as an outcome may detract attention from other evidence-based quality measures that can be more readily improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation